A clinical case of asymptomatic drug-induced thrombocytopenia - A. A. Zolotarev; E. A. Pyhtunova; O. Yu. Trifonova; S. I. Kseneva; V. V. Udut (Сибирский научный медицинский журнал)
Thrombocytopenia is a condition in which the level of platelets in the blood decreases and becomes less than 150×109/L. This can lead to an increased risk of bleeding. One of the causes of thrombocytopenia may be medication; its association with the use of more than 300 drugs has now been documented. The pathogenesis of such, drug-induced thrombocytopenia (DITP), is described as a consequence of direct cytotoxic effects of drug on megakaryocytes, which leads to increased platelet destruction in the bloodstream or dysfunctional thrombopoiesis. In the diagnosis of DITP the leading role belongs to the clinical approach: first of all, it is carried out on the basis of data of drug history and a minimum set of laboratory tests, including counting the number of platelets in the blood and determining the clotting time. Since thrombocytopenia may be associated with the risk of serious bleeding, its timely diagnosis is of key importance for determining the tactics of therapeutic intervention. We present a clinical case of DITP, after the combined use of drugs of different groups – statin, xanthine oxidase inhibitor, cytostatic drug of antimetabolite group, non-selective beta- adrenoblocker and two non-steroidal anti-inflammatory drugs with different mechanism of action. The described case showed that to avoid polypharmacy in patients with DITP it is necessary to assess hemostatic potential by low-frequency piezotromboelastography, because even in conditions of insufficient platelet count they can provide preserved functional ability to maintain hemostasis.